Adjuvants for Coronavirus Vaccines - Liang, Zhihui; Zhu, Haoru; Wang, Xin; Jing, Bo; Li, Zifan; Xia, Xinyu; Sun, Hongwu; Yang, Yun; Zhang, Weiting; Shi, Li; Zeng, Hao; Sun, Bingbing (Frontiers in Immunology, 2020)
Confronting the current severe situation of COVID-19 pandemic, vaccines utilizing various platforms are currently in the development pipeline. Adjuvants are key components in subunit and certain inactivated vaccines to promote stronger and long-lasting specific immune responses. Examining the history of coronavirus vaccine development, only limited adjuvants, e.g., aluminum salts, emulsions, TLR agonists, etc., have been formulated in SARS-CoV, MERS-CoV and currently SARS-CoV-2 vaccines in experimental & preclinical studies. However, there still lacks systemic knowledge for the adjuvants tested in various coronavirus vaccines. This paper presents an overview of adjuvants that have been formulated in reported coronavirus vaccine studies, which hopefully will assist the design and selection of adjuvants with optimal efficacy and safety profiles for COVID-19 vaccines.